Multicultural and peace classrooms. Two proposals for a post-conflict country - Bolaños Motta, José Ignacio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
This reflection paper exposes some of the missionary senses of the Colombian education at the beginning of the 21st century. In the first instance, a historical and critical reflection on educational phenomena is carried out in order to understand the citizenship types built in the country. This is perhaps a utopian perspective of a culture for peace based on considering the terms of a post-conflict policy. According to the above, we attempt to rethink the citizen's imaginary from a historical perspective by means of a bibliographic and documentary inquiry, from which two proposals regarding the national education emerge: the first one claims that the Colombian school must be prepared to make a proposal of multicultural nature. The second one, postulated from the method, as the multicultural condition that must reaffirm a perspective of peace. With the presentation of these ideas, we hope to evidence the possibility of joining the two political tendencies of the Colombian school in a single proposal that, from the understanding of the difference, foster the social skills necessary for the generation of a peace culture.